The Charter and General Ordinances of the Town of Lexington, Virginia, at 108, ch. 70, § 1 (1892) - (:unkn) unknown (General Publisher, 1873)
If any person, in any street or public alley, shall fire or discharge any gun, pistol or other fire-arms, or play bandy, or throw snow balls, stones or other missiles, or discharge arrows from a bow or cross-bow, he shall be fined not less than one dollar nor more than five dollars.
--
Keywords: DISCHARGE